Pola Pengelolaan Sampah di Kelurahan Bandarharjo - Lucky Mutiara Pindan Rattekarua; Widjonarko Widjonarko (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Due to rapid urbanization in Semarang, as indicated by high population growth affect many problems. One of the problems faced is the higher production of solid waste. On the other hand, the government has enough capability to overcome high productivity.  This problem generally occurs in poor residential areas, including in Bandarharjo. This district is the most slum settlements with complex environmental problems (Suwanda, 2000). This district also has a different waste management, the environment there that have got solid waste management and which have not. This condition is interesting to study because there is a difference between the environmental waste management mechanism, whereas people living entities therein are equally dominated by the poor. Therefore, we need research that aims to assess the pattern of waste management. In every neighborhood divided into twelve (12) RW is carried out a comparative study of how the pattern of waste management. The method used is descriptive qualitative. The research results indicate that poor waste management due to the unintegrated aspects that play a role in waste management, among other aspects of operational technical, institutional, financing aspects, regulatory aspects and aspects of community participation.